'Beneficial' Delays in Debt Restructuring Negotiations - Bi, Ran (IMF Working Papers; Working Paper, 2008)
Delays in debt restructuring negotiations are widely regarded as inefficient. This paper argues that delays can allow the economy to recover from a crisis, make more resources available for debt settlement, and enable the negotiating parties to enjoy a larger "cake". Within this context, therefore, delays may be "beneficial". This paper explores this idea by constructing a dynamic model of sovereign default in which debt renegotiation is modeled as a stochastic bargaining game based on Merlo and Wilson's (1995) framework. Quantitative analysis shows that this model can generate an average delay length comparable to that experienced by Argentina in its most recent debt restructuring.